Sul ‘Nerone’ di Boito - Guccini, Gerardo (Drammaturgia, 2017)
The essay examines the role of Nerone in Arrigo Boito’s biography and the compositional process of this unfinished work. An atypical and experimental creative process, that did not proceed from selecting the theme to writing the libretto, composing the music and finally projecting the staging, because these steps continued to reshape themselves whilst interacting reciprocally. Boito worked on Nerone by combining three creative modalities: as dramaturg he drew from historical and literary research and from theoretical reflection projects and elements useful to the work of the man of letters Boito and of the composer Boito. On the other hand, the man of letters Boito and the composer Boito greatly widened the scope of the dramaturg Boito, who used to consider transitory and replaceable his intermediate results: both music and written scenes were frequently put aside in order to let the work’s inner logic find its way. The compositional process of Nerone produced an hypertext consisting of information blocks partly preserved and partly destroyed. They included written texts (dialogues, stage directions, quotations, short treatises on harmony and prosody), still images (scenery sketches and other figures), projects of images and figures in motion (plans, or colour and tonal combinations), sounds (the composed music). Nerone, at the same time an unfinished and an experimental work, puts Boito among the forerunners of the twentieth century avant-gardes.